Efeito da obstrução gerada pela densidade da vegetação do sub-bosque sobre morcegos frugívoros e animalívoros catadores (Chiroptera: Phyllostomidae) na Amazônia Central, Brasil - Silva, Rodrigo Marciente Teixeira da (Instituto Nacional de Pesquisas da Amazônia - INPA, 2012)
Cluttered vegetation structure demands maneuverable fight for bats. Based on wing morphology, it has been suggested that animalivorous bats have better flight performance in cluttered areas than others trophic guilds. I related density of understory vegetation as a measure of clutter to species composition of Phyllostomidae bats assemblages. I expected find a great contribution of animalivores bats to species composition in mature-forest sites with denser understory. The study was carried out in Purus-Madeira interfluves, along BR-319 highway where eight sample units at least 40 km apart and constituted for ten permanents plots were sampled. I employed ordination techniques and generalized linear models to make inferences about habitat use by phyllostomid bats along a clutter gradient. With a capture effort of 3,840 nets-hour, 511 bats of 4 families (Emballunoridae, Phyllostomidae, Vespertilionidae and Thyropteridae) and 27 species were captured, of which 12 were frugivores (n=414 captures) and 10 animalivores (n=70 capturas). The number of species was reduced from 16 to 7 along a gradient of vegetation obstruction among 53% to 73%. This negative effect occurred for both trophic guilds. Assemblages showed a nested pattern along the clutter gradient, with animalivorous bats tending to occur in sites with denser vegetation. The filter effect on body size alone was not sufficient to explain the structure of bat assemblages in relation to clutter. The effect of clutter differed between foraging guilds. Differences in availability and distribution of food resources in forest sites with different degrees of clutter may affect the proportion of different guilds that use cluttered sites.
Keywords: Morcegos; Morcegos frugívoros; Estrutura trófica